Proceedings of the Fourth Prasasti International Seminar on Linguistics (Prasasti 2018) 2018
DOI: 10.2991/prasasti-18.2018.35
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Bundles in Indonesian and English Undergraduate Thesis Abstracts

Abstract: The present study investigates Indonesian and English lexical bundles (LBs) used by Indonesian learners in their thesis abstracts. It aims to examine (1) the most common lexical bundles in the Indonesian and English undergraduate thesis abstracts, (2) similarities/differences in terms of form and functions, and (3) possible factors for the use of LBs in the students' abstracts. The data were obtained from a corpus of 140 abstracts written by Indonesian undergraduate students from Natural Science and Social Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Students used lexical bundles as discourse organizers and referential expressions in the introduction part. On the other side, Samodra & Pratiwi (2018) identified three and four-word combinations in undergraduate thesis abstracts of Indonesian and English. They found that research-oriented bundles dominated the text.…”
Section: Lexical Bundlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Students used lexical bundles as discourse organizers and referential expressions in the introduction part. On the other side, Samodra & Pratiwi (2018) identified three and four-word combinations in undergraduate thesis abstracts of Indonesian and English. They found that research-oriented bundles dominated the text.…”
Section: Lexical Bundlesmentioning
confidence: 99%
“…In theses, students can use lexical bundles based on its structure and function, which may vary in every part or chapter. Functionally, research-oriented lexical bundles are the biggest portion in the abstracts of student theses (Samodra & Pratiwi, 2018). Meanwhile, in the different part of student theses, Findings and Discussion section, Wachidah et al (2020) concluded that text-oriented function is the most common lexical bundles based on physical data collection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the research on Indonesian lexical bundles, so far to our knowledge, it has not much been conducted. Samodra and Pratiwi (2018) investigated and compared lexical bundles of Indonesian and English on undergraduate thesis abstracts. They found that the Indonesian lexical bundles were dominated by phrase penelitian ini 'this research' and English bundles were dominated by the phrase this research 'penelitian ini'.…”
Section: Introductionmentioning
confidence: 99%